Usage of spicy aromatic plants of the flora of Armenia in the national cuisine - Sargsyan, M. (Regulatory Mechanisms in Biosystems, 2023)
Since ancient times, Armenians have used wild plants in their diet in both fresh and processed forms. Their gastronomic traditions, knowledge about useful plants, and methods of their application have been passed from generation to generation. In this review we analyse the species composition of plants that are used as spices in the national cuisine, how many there are, and what prospects there are for their use. Field surveys were conducted to collect ethnobotanical data of the use of aromatic plants in all of regions in Armenia during the years 2016–2022. 58 informants (42 women and 16 men) were interviewed after obtaining their prior informed oral consent. The informants included farmers, housewives and cooks engaged in preparing the national cuisine. All the informants participated voluntarily and shared their life experience, knowledge received from grandmothers and their professional skills. For the first time, a list of spicy plants of the flora of Armenia which were used in the preparation of national dishes is presented. Some species are no longer used, because classic spices are already available for sale, but some species of plants are still used today as a seasoning in national dishes. In the flora of Armenia there are 142 species of spicy aromatic plants belonging to 115 genera and 46 families. Studies have shown that the largest number of spicy-aromatic plants grow in Central and Southern Armenia (Armeno-Iranian floral province). On the basis of this rich plant resource, it is possible to organize the cultivation of organic spicy plants and spices in order to use them in various branches of the food industry. The recollected knowledge of our ancestors in the area of cheesemaking, winemaking, beermaking, combining centuries of experience with today’s new technologies and use of spice plants can be used to develop the country’s economy.